Stability of inner dump slope and analytical solution based on circular failure: Illustrated with a case study. (January 2020) - Wang, Zhiliu; Liu, Bo; Han, Yanhui; Wang, Jian; Yao, Biao; Zhang, Peng
Abstract: The analytical solution of factor of safety (FoS) accommodating the effects of groundwater seepage on the stability of the dump slope was seldom studied in the existing dump stability analysis methods. In this work, the analytical solution of FoS was developed to accommodate the effects of groundwater on the stability of the dump slope. The parameter analysis is carried out and the results show the FoS of slope stability decreases until a stable value is reached with the groundwater level increasing. The reduction of FoS vs. groundwater level can be described by an inverse function, in which FoS reduction rate decreases with increasing groundwater level. FoS = 1 can be considered as the inflection point of the rate change. The analytical solutions are validated in a case study for Shengli #1 open-pit mine, in which field tests were performed to measure the distribution of the flow field. In this case study the influence of groundwater on the FoS of the selected inner dump slope was analyzed using FLAC 3D and SLOPE/W and our analytical solutions for a number of engineering situations and consistent and comparable results were obtained.